The role of innovation, entrepreneurial self-efficacy and local uniqueness on marketing performance in small and medium-sized restaurants. Issue 6 (1st November 2020) - Najib, Mukhamad; Septiani, Stevia; Nurlaela, Siti
ABSTRACT: The growth of the food service business in Indonesia cannot be optimized by small and medium restaurants due to a lack of innovation and entrepreneurial skill. This present study combines marketing and entrepreneurship literature and explores the link among innovation, entrepreneurial self-efficacy and marketing performance. Using a purposive sampling methodology, data were collected from 124 respondents of small and medium-sized restaurants in Bogor city, Indonesia. This study used Structural Equation Modeling to analyze the influences of entrepreneurial self-efficacy, innovation and local uniqueness on marketing performance. The findings indicate that innovation activity has a direct significant influence on marketing performance. This study also indicates that entrepreneurial self-efficacy positively influences marketing performance reflected by increasing sales, profits and number of customers. In addition, local uniqueness, which is an intermediary variable, is not affected by innovation activities and does not directly affect marketing performance. Even though this study supports most hypotheses, two out of six were not. As such, the results of this study provide important practical insights as well as interesting contributions to the theoretical advancements in entrepreneurship and marketing especially in the setting of small and medium-sized restaurants.